Recyclable hemp hurd fibre-reinforced PLA composites for 3D printing - M.D.H. Beg; K.L. Pickering; John O. Akindoyo; C. Gauss (Journal of Materials Research and Technology)
In this study, 3D printing filaments were produced from hemp hurd fibre-reinforced polylactide (PLA) composites. Hemp hurd microfibres were obtained through alkaline digestion followed by a bleaching treatment and were used to produce PLA-based composites with 20–40 wt% fibre content for fused deposition modelling. Tensile testing of 3D printed composites revealed a gradual increase of Young's modulus with the addition of fibres, reaching a maximum of 7.1 GPa for the 40 wt% composite - a two-fold increase to neat PLA. However, tensile strength was only improved for the 20 wt% formulation, with an increase of 8% in comparison with neat PLA. Nevertheless, the thermo-mechanical properties of the composites were significantly enhanced with the addition of fibres. In addition, physical objects were printed from the recycled filaments to assess their recyclability and printability. It was found that the recycled filaments maintained comparable mechanical properties and printability after three recycling cycles.